HIV infection and bone disease. (6th June 2016) - Compston, J.
Abstract: The success of antiretroviral therapy in treating HIV infection has greatly prolonged life expectancy in affected individuals, transforming the disease into a chronic condition. A number of HIV‐associated non‐AIDS comorbidities have emerged in the ageing HIV‐infected population, including osteoporosis and increased risk of fracture. The pathogenesis of fracture is multifactorial with contributions from both traditional and HIV‐specific risk factors. Significant bone loss occurs on initiation of antiretroviral therapy but stabilizes on long‐term therapy. Fracture risk assessment should be performed in HIV‐infected individuals and bone mineral density measured when indicated. Lifestyle measures to optimize bone health should be advised and, in individuals at high risk of fracture, treatment with bisphosphonates considered.